Pengaruh Pencemaran Logam Berat Timbal (Pb) dan Ekskresi Iodium Urine (EIU) Terhadap Kejadian Stunting Pada Anak di Surabaya - LEONI; WIENTA DIARSVITRI; VERNA BIUTIFASARI (HANG TUAH MEDICAL JOURNAL, 2021)
ABSTRACT Background : The existence of children, living in the coastal area with such risk of suffering from lead (Pb) intoxication, is still considered high. This pollutant plays a role in children’s growth and development. Lead (Pb), existing in our body, would directly reduce the amount of iodine that is absorbed by our body and in the end, would reduce the number of hormones affecting both physical growth and mental development for instance Growth Hormone, Thyroid Hormone, and Insulin-like Growth Factor (IGF-1). Other than Lead (Pb), growth is affected by another factor such as heredity, nutrition, and physical activity. This study serves the purpose of determining the effect of lead (Pb) pollution and Urinary Iodine Concentration (UIC) on the occurrence of stunting in children at the age of 25-60 months old at the urban village of Kedung Cowek Surabaya. Methods : observational analytic study a cross-sectional study design, by using a quantitative method which was used on 27 mothers whose children are 25-60 months old at Posyandu RW 2 and RW 3 urban village of Kedung Cowek Surabaya. The sample was chosen using a purposive sampling method. Data was collected through weight and height measurement, age, KMS (Card Towards Health), KIA (Kartu Ibu dan Anak), and questionnaires done by interviewing. Bivariate analysis was performed using Kruskal-Wallis. Results : Based on the laboratory test, it is shown that there’s no lead (Pb) pollution detected in seawater with the final result of 0,00035 mg/L (polluted > 0,008 mg/L). Based on Kruskal-Wallis, Urinary Iodine Concentration (UIC) doesn’t influence the occurrence of stunting based on deviation standard and nutritional status from the Ministry of Health (p = 0,409). Conclusion : There is no effect of lead (Pb) pollution and Urinary Iodine Concentration (UIC) on the occurrence of stunting in children at the age of 25-60 months old at the urban village of Kedung Cowek Surabaya.